A Proposed Scheme of Fishing Quota Allocation to Ensure the Sustainable Development of China’s Marine Capture Fisheries - Liu, Honghong; Peng, Daomin; Yang, Hyun-Joo; Mu, Yongtong; Zhu, Yugui (Frontiers in Marine Science, 2022)
The sustainable development of marine capture fisheries (MCFs) plays a significant role in food security, economic development and employment stability. The lack of information on the sustainability of MCFs, along with the inadequate management of fisheries output controls, has weakened China's efforts towards a national catch limit target of no more than 10 million tons from capture fisheries until 2020. Further, overfishing and fishery conflicts still exist. In order to try and resolve the above problems and achieve the sustainable use of fishery resources, an evaluation of the development status of these fisheries based on the coupling coordination model has been undertaken. The results show that the social, economic and biological systems of MCFs in coastal areas of China interact with each other, while their development is not coordinated, and regional differences exist. Taking the catch share program as a breakthrough methodology to resolve inconsistencies, this study integrates the socio-economic indicators. The results under different allocation schemes suggest that the multi-factor scheme is more equitable than the single-factor scheme, which enhances the fairness of the initial distribution.